Update on the Transmission of Zika Virus Through Breast Milk and Breastfeeding: A Systematic Review of the Evidence - Centeno-Tablante, Elizabeth (Viruses, 2021)
We systematically searched regional and international databases and screened 1658 non-duplicate records describing women with suspected or confirmed ZIKV infection, intending to breastfeed or give breast milk to an infant to examine the potential of mother-to-child transmission of Zika virus (ZIKV) through breast milk or breastfeeding-related practices. Fourteen studies met our inclusion criteria and inform this analysis. These studies reported on 97 mother–children pairs who provided breast milk for ZIKV assessment. Seventeen breast milk samples from different women were found positive for ZIKV via RT-PCR, and ZIKV replication was found in cell cultures from five out of seven breast milk samples from different women. Only three out of six infants who had ZIKV infection were breastfed, no evidence of clinical complications was found to be associated with ZIKV RNA in breast milk. This review updates our previous report by including 12 new articles, in which we found no evidence of ZIKV mother-to-child transmission through breast milk intake or breastfeeding. As the certainty of the present evidence is low, additional studies are still warranted to determine if ZIKV can be transmitted through breastfeeding.